Nurses’ Communicating with Patients in Peripheral and Border Areas in Indonesia: A Phenomenology Study - Petrus Kanisius Siga Tage; Herliana Monika Azi Djogo; Yulia M.K Letor; Maria Yoanita Bina; Rahmawati Rahmawati (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: Communication is an important part of nursing care. However, Indonesian nurses still feel communication problems due to cultural and linguistic differences, especially in peripheral and border areas.